THE INFLUENCE OF COMIC STRIPS MEDIA IN TEACHING WRITING SKILL TO THE TENTH GRADE STUDENTS IN CIANJUR - Suherman, Syifa Butsainah Ulfa; Kareviati, Evie (PROJECT (Professional Journal of English Education), 2021)
Writing is an important skill for students because it helps them in their life but sometime they have difficulties when they start to writing. Therefore, the teacher must be able to find and use the right strategies for teaching writing activity especially choosing teaching media. One of the media that can be used in teaching writing is comic strips. The objective of this research is to find out whether there is an influence of using comic strips media to improve writing skill in the tenth grade students. This research employed pre-experimental design and used test questions as the instrument. The sample was the tenth grade students in one of SMKN in Cianjur, consisting of 36 students. The research compared the mean of the pre-test and post-test to identify the influence of comic strips media in improving writing skill.